Healthy Food Marketing Across Consumer and Retail Levels: A Descriptive Comparative Analysis of Perception - James Tandy (Universitas Pelita Harapan, 2026)
Healthy food marketing influences consumers and retailers across three stages of the decision-making process. The purpose of the study is to describe and compare how marketing cues shape consumer perception, how specific strategies influence purchase decisions, and how store level conditions affect the adoption of health-oriented marketing practices. Three peers reviewed articles form the basis of the analysis. The first article, by Li et al. (2024), explains about packaging cues related to taste and health shape consumers' beliefs about product healthfulness and their purchase intentions. Their findings show that taste-focused cues increase purchase intention but may reduce perceived healthiness, while health-focused cues enhance health perceptions across product types. The second article, by Vidal and Castellano (2022), identifies the strategies that influence purchase intention. Their work highlights the effect of front of pack labels, nutritional information, natural quality cues, and emotional appeals on consumer choice. The third article, by Houghtaling et al. (2019), reviews the factors that influence food store owners' and managers' willingness to use healthy choice architecture and marketing mix strategies. Their findings show that adoption depends on customer demand, profit expectations, staff capacity, and operational constraints. Consumers form health beliefs from marketing cues, these beliefs influence responses to targeted strategies, and store operators adjust their marketing mix in response to customer behavior and financial expectations. This study contributes an integrated understanding of how perception, strategy, and retail decision making interact, offering insights for marketers, public health planners, and store managers who aim to strengthen healthy food environments.